(untitled) (REMUNOM, 2026)
Sapodilla is an Amazonian fruit with relevant nutritional and functional potential yet remains underexplored. This study aimed to characterize the physical and physicochemical properties of fruits and pulps marketed in Belém do Pará and compare two harvests using statistical analyses. pH, electrical conductivity, moisture, density, soluble solids, and acidity were determined following official methods. The results showed that sapodilla fruits are rounded and have a good pulp yield, with physicochemical properties similar to those found in the literature, and presented values for some variables that were not found in the literature. Furthermore, only the acidity of the pulp showed a significant variation between the two harvests. These findings highlight the importance of physicochemical profiling for quality control and industrial standardization.